Enhancing Adolescent Mental Well-Being through Family Emotional Support Education (JURNAL PENGMAS KESTRA (JPK), 2025)
Adolescent depression is a serious mental health issue that can affect quality of life, academic achievement, and social interactions. A key factor influencing adolescents’ psychological well-being is family emotional support, including attention, empathy, effective communication, and motivation to cope with life stressors. Lack of parental awareness regarding the importance of emotional support often results in adolescents experiencing stress or psychological pressure without adequate attention or intervention. Consequently, they are more vulnerable to social isolation, low self-esteem, and behaviors that may endanger themselves. This Community Service Program (PkM) was designed to empower families through interactive education and simulation practices, enabling them to provide appropriate emotional support and prevent depression in adolescents. Respondents included 40 families with adolescents aged 13–18 years, selected through purposive sampling. Activities involved pre-tests, brief lectures, group discussions, emotional communication simulations, post-tests, and evaluations. Results demonstrated significant improvement, with participants exhibiting high knowledge increasing from 12.5% to 70%, high ability from 15% to 65%, and high awareness of depression signs from 15% to 75%. These findings confirm that combining interactive education with simulation practices effectively enhances family understanding, skills, and awareness, playing a crucial role in preventing adolescent depression and supporting their overall mental health.